A STUDY ON WORK AND FAMILY LIFE BALANCE (WLB) AMONG WOMEN PUBLIC PROSECUTORS IN JUDICIARY SYSTEM OF MAHARASHTRA (International Journal of Food and Nutritional Sciences, 2022)
The legal profession has gained utmost importance and also it is one of the most adventurous as well as exciting career. In General the lawyers have high admiration in our society, and also there remains the faith that when all else fails, one can still take remedy to the legal system. In such a valued profession women could not occupy a valuable space. The main reason for less percentage of women in the legal system is work life imbalance. The work and family life imbalance leads to stress and overall dissatisfaction. Hence this research has under taken to find out the reasons which make work and family life imbalance and its impact on job involvement with reference to women public prosecutors with reference to Maharashtra. The researcher has adopted descriptive research design and a purposive sampling technique which comes under non-probability sampling method has employed and sample size is 156 respondents. Both primary and secondary data are collected. The data are analyzed using SPSS. Finally it is showed that women advocates balance their work and family life at moderate level. Hence the study concludes by suggesting some measures to enhance the job involvement through effective work and family life balance.